Zirconia ceramic sample to be detected as well as preparation method and application thereof

Through the process of grinding, polishing and heating corrosion, the damage and low efficiency of zirconia ceramic materials in the existing technology are solved, and damage-free, clear microstructure appearance and high-accuracy microscopic detection are achieved. .

CN119124783AInactive Publication Date: 2024-12-13KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411360912.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ceramic crystal morphology analysis methods, especially thermal corrosion methods, have problems of damage and complex operation on the microstructure of zirconia ceramic materials, and the chemical corrosion method has strong corrosion resistance for powders with smaller particle sizes. The sample is not effective.

Method used

Using the process flow of grinding, polishing and heating corrosion, by optimizing the grinding speed, rotation angle and polishing steps, combining the heating rate and insulation time of heating corrosion, a microstructure of zirconia ceramics with smooth surface and clear and uniform grain boundary profile are obtained. Avoid the use of chemical corrosion and the damage of thermal corrosion.

Benefits of technology

The microstructure of zirconia ceramics is realized without damage, simplifies the operation process, improves the accuracy and efficiency of microscopic detection, and ensures the flatness of the surface and the clarity of the tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119124783A_ABST
    Figure CN119124783A_ABST
Patent Text Reader

Abstract

The invention provides a zirconia ceramic sample to be detected and a preparation method and application thereof, the preparation method comprises the following steps: (1) grinding and polishing a zirconia ceramic sample in sequence to obtain a pretreated zirconia ceramic sample; and (2) heating and corroding the pretreated zirconia ceramic sample in the step (1) to obtain the zirconia ceramic sample to be detected capable of showing the microstructure. According to the method, the zirconia ceramic with a flat and smooth surface and a clear grain boundary contour can be obtained, the corrosion process is more stable and controllable, the microstructure and tissue of the ceramic surface are clearly highlighted, the problems that the surface of the zirconia ceramic is possibly damaged, the corrosion effect is fuzzy and unclear and the like due to the existing hot corrosion and chemical corrosion technologies are avoided, and the method is suitable for industrial production. Therefore, the accuracy of crystal grain crystal phase result observation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of analysis and detection, and in particular to a zirconium oxide ceramic sample to be tested, a preparation method thereof and an application thereof. Background Art

[0002] Zirconia ceramics are a high-performance structural ceramic material. They are widely used in various industrial fields because of their advantages such as high melting point, high strength, high hardness, corrosion resistance and wear resistance. The grain morphology, size and distribution of ceramic materials will have a significant impact on the mechanical, optical and electrical properties of the material. Therefore, clear imaging of the microstructure of ceramic materials is a prerequisite for characterizing the microscopic properties of ceramics. At present, the commonly used processing methods for analyzing the crystal morphology of ceramics mainly include chemical corrosion and thermal corrosion. The chemical corrosion method is simple and convenient to operate and has high efficiency, but the effect is not obvious for powders with small particle size and ceramic samples with strong corrosion resistance. The thermal corrosion method can clearly show the microstructure of ceramic materials, but its corrosion conditions are not suitable for exploration, and the requirements for equipment and heating processes are very strict. The existing heat treatment methods often require higher temperatures and longer times to produce microcracks on the surface of zirconia ceramics. Although this method can observe the surface microstructure and organization of zirconia ceramics, its operation process is complicated and requires precise control of temperature and time. In addition, the surface of zirconia ceramics may be damaged during thermal corrosion. In addition, although the existing metallographic analysis methods can obtain the microstructure image of the material, they often cannot obtain clear images, which may affect the accuracy of the analysis results.

[0003] Therefore, in order to accurately and clearly understand the grain size and distribution of zirconia ceramics, it is crucial to optimize the current ceramic thermal corrosion method.

[0004] At present, the commonly used processing methods for analyzing the morphology of ceramic crystals mainly include: chemical corrosion method and thermal corrosion method. Chemical corrosion method is a commonly used method currently. Generally, a mixed solution of strong acid HF, HCl or HNO3 is used to treat the surface of the ceramic sample, and the morphology is formed by the difference in the degree of corrosion of the grain boundary and the grain by the strong acid. This method is simple, convenient and efficient, but the effect is not obvious for powders with smaller particle size and ceramic samples with strong corrosion resistance. Thermal corrosion is to place the sample in a high-temperature furnace and realize the imaging of the grains by volatilization of grain boundary elements. Because the thermal corrosion conditions of grain boundaries and grains are significantly different, they volatilize more thoroughly after reaching the grain boundary corrosion conditions, and the grain boundary is prominent. The conditions of thermal corrosion are not easy to explore, and the requirements for equipment and heating process are very strict.

[0005] CN118032473A discloses a method for preparing a metallographic sample and displaying a structure of a zirconia ceramic material. The zirconia ceramic is subjected to steps such as inlaying, grinding, polishing, and chemical etching to obtain a metallographic sample with a smooth surface and clear structure. However, this method still requires the use of chemical etching, and zirconia ceramics have high chemical stability and strong corrosion resistance, so the requirements for the ratio, concentration, and temperature of the etching solution are very high.

[0006] In summary, it is necessary to develop new methods for corroding zirconia ceramic materials. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a zirconia ceramic sample to be tested, a preparation method and application thereof, by grinding, polishing and thermally corroding the zirconia ceramic in sequence, and further optimizing and improving the process, a zirconia ceramic microstructure with a smooth surface, clear and uniform grain boundary contours, and no damage can be obtained, which provides convenience for subsequent microscope detection.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a zirconia ceramic sample for detecting microstructure, the preparation method comprising the following steps:

[0010] (1) The zirconia ceramic sample is ground and polished in sequence to obtain a pre-treated zirconia ceramic sample;

[0011] (2) The pre-treated zirconia ceramic sample in step (1) is heated and corroded to obtain a zirconia ceramic sample to be tested that can display a microstructure.

[0012] The present invention adopts a process flow of grinding, polishing and heating corrosion. After grinding and polishing, a zirconia ceramic with a smooth and flat surface can be obtained. After subsequent heating corrosion, the grain boundary contours of the zirconia ceramic sample can be clearly and evenly displayed, and the microstructure of the zirconia ceramic is not damaged, which is convenient for subsequent microscopic observation.

[0013] Preferably, the zirconia ceramic sample in step (1) is a zirconia ceramic sample that has been cold-mounted in a mold.

[0014] Preferably, the grinding rotation speed is 200-400 rpm, for example, it can be 200 rpm, 223 rpm, 245 rpm, 267 rpm, 289 rpm, 312 rpm, 334 rpm, 356 rpm, 378 rpm or 400 rpm.

[0015] It is worth noting that the grinding speed in the present invention is very critical. The inventors have found through various studies that even if the same process is used, when the grinding speed is not between 200 and 400 rpm, it is difficult to obtain a smooth surface that does not damage the microstructure of the zirconia ceramic.

[0016] Preferably, during the grinding process, the zirconia ceramic sample is rotated every 3 to 8 minutes, for example, 3 minutes, 3.6 minutes, 4.2 minutes, 4.7 minutes, 5.3 minutes, 5.8 minutes, 6.4 minutes, 6.9 minutes, 7.5 minutes or 8 minutes.

[0017] Preferably, the rotation angle is 88° to 92°, for example, 88°, 89°, 90°, 91° or 92°.

[0018] The difficulty of the present invention is how to make the microstructure visible without damaging the microstructure on the surface, while ensuring that the surface is smooth and uniform; it is difficult to achieve a smooth and uniform surface simply by grinding. The researchers found that the zirconia ceramic sample is rotated every 3 to 8 minutes during the grinding process, which can ensure a more uniform grinding, and the angle of each rotation is preferably 90°, so as to eliminate the unevenness caused by the previous grinding in a specific direction. Through research, it is found that by rotating at intervals, combined with polishing and heat treatment processes, a zirconia ceramic material with a smooth surface can be obtained.

[0019] Preferably, the grinding comprises at least 3 sub-grinds, preferably 4 sub-grinds.

[0020] Preferably, the grinding time of each sub-grinding is 15 to 30 min, for example, it can be 15 min, 17 min, 19 min, 20 min, 22 min, 24 min, 25 min, 27 min, 29 min or 30 min.

[0021] Preferably, as the grinding proceeds, the mesh size of the sandpaper used for the sub-grinding gradually increases.

[0022] Preferably, the mesh difference between the sandpapers used for adjacent sub-grinding is 200-400 meshes, for example, it can be 200 mesh, 223 mesh, 245 mesh, 267 mesh, 289 mesh, 312 mesh, 334 mesh, 356 mesh, 378 mesh or 400 mesh.

[0023] Preferably, when the grinding is performed with four sub-grinding steps, the mesh sizes of the sandpaper used for each sub-grinding step are 200-260 meshes, 350-450 meshes, 750-850 meshes and 900-1100 meshes respectively.

[0024] Among them, 200-260 mesh, for example, can be 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh or 260 mesh, etc.; 350-450 mesh, for example, can be 350 mesh, 360 mesh, 365 mesh, 370 mesh, 380 mesh, 390 mesh, 400 mesh, 410 mesh, 420 mesh, 430 mesh, 440 mesh or 450 mesh, etc.; 750-850 mesh, for example, can be It can be 750 mesh, 760 mesh, 770 mesh, 780 mesh, 790 mesh, 800 mesh, 810 mesh, 820 mesh, 830 mesh, 840 mesh or 850 mesh, etc.; and 900-1100 mesh, for example, it can be 900 mesh, 920 mesh, 930 mesh, 950 mesh, 970 mesh, 980 mesh, 990 mesh, 1000 mesh, 1020 mesh, 1050 mesh, 1060 mesh or 1100 mesh, etc.

[0025] In addition to rotating the direction during the grinding process, the present invention also requires at least four grindings with different mesh sizes, and the grinding mesh size is controlled within the above range, so as to obtain a smooth and uniform surface without damaging the microstructure.

[0026] Preferably, the polishing includes at least 3 sub-polishings, preferably 3 sub-polishings.

[0027] Preferably, when the polishing is performed by three sub-polishings, the first sub-polishing is performed by using a diamond polishing paste of model W14, the second sub-polishing is performed by using a diamond polishing paste of model W7, and the third sub-polishing is performed by using a diamond polishing paste of model W1.

[0028] In the present invention, it is preferred to use the above-mentioned polishing pastes in sequence to obtain a zirconium oxide ceramic sample with better structure.

[0029] Preferably, the preparation method further comprises a cleaning and drying process provided between step (1) and step (2), wherein the cleaning and drying process comprises pre-treating the zirconia ceramic sample by ultrasonic cleaning and drying in sequence.

[0030] Preferably, the heating rate of the heating corrosion is 4.5-5.5°C / min, for example, it can be 4.5°C / min, 4.7°C / min, 4.8°C / min, 4.9°C / min, 5°C / min, 5.1°C / min, 5.2°C / min, 5.3°C / min, 5.4°C / min or 5.5°C / min, etc.

[0031] Preferably, the final temperature of the heating corrosion is 190-210°C lower than the sintering densification temperature of the zirconia ceramic sample, for example, it can be 190°C, 193°C, 195°C, 197°C, 199°C, 202°C, 204°C, 206°C, 208°C or 210°C.

[0032] Preferably, the final temperature of the heated corrosion is 1300-1400°C, for example, it can be 1300°C, 1312°C, 1323°C, 1334°C, 1345°C, 1356°C, 1367°C, 1378°C, 1389°C or 1400°C.

[0033] Preferably, the heating corrosion is kept at the final temperature for 0.8 to 1.5 h, for example, it can be 0.8 h, 0.88 h, 0.96 h, 1.04 h, 1.12 h, 1.19 h, 1.27 h, 1.35 h, 1.43 h or 1.5 h.

[0034] The present invention further preferably controls the heating corrosion time within the above range, and can obtain a zirconia ceramic sample to be tested with a better microstructure, can effectively realize the thermal corrosion of zirconia ceramics, and can clearly observe and analyze the microstructure and organization of its surface. Moreover, compared with the prior art, the insulation time is as long as 2 hours or more, and the insulation time of the present application is only 0.8 to 1.5 hours. The insulation time is short, and no micro cracks are generated on the surface of the zirconia ceramic, and the surface of the zirconia ceramic is not damaged. A clear image can be obtained, and the accuracy of the analysis result is higher.

[0035] Preferably, the preparation method further comprises: cooling to room temperature after the heating and etching.

[0036] Preferably, the cooling rate is 3 to 8°C / min, for example, 3°C / min, 3.6°C / min, 4.2°C / min, 4.7°C / min, 5.3°C / min, 5.8°C / min, 6.4°C / min, 6.9°C / min, 7.5°C / min or 8°C / min, etc.

[0037] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0038] (1) The zirconia ceramic sample is first ground at 200-400 rpm. During the grinding process, the zirconia ceramic sample is rotated 88-92° every 3-8 minutes. The grinding includes four sub-grindings (the sandpaper mesh numbers used are 200-260 mesh, 350-450 mesh, 750-850 mesh and 900-1100 mesh, respectively). The sub-grinding time is 15-30 minutes to obtain a ground sample;

[0039] The ground sample is sequentially subjected to three sub-polishing steps, wherein the first sub-polishing step is performed using a diamond polishing paste of model W14, the second sub-polishing step is performed using a diamond polishing paste of model W7, and the third sub-polishing step is performed using a diamond polishing paste of model W1, to obtain a pre-treated zirconia ceramic sample;

[0040] (2) the pre-treated zirconia ceramic sample is ultrasonically cleaned and dried in sequence to obtain a dried sample;

[0041] (3) After the drying in step (2), the sample is heated to 1300-1400°C at a heating rate of 4.5-5.5°C / min and kept at the final temperature for 0.8-1.5h to perform heating corrosion, and then cooled to room temperature at 3-8°C / min to obtain a zirconium oxide ceramic sample to be tested that can show a microstructure.

[0042] In a second aspect, the present invention provides a zirconia ceramic sample to be tested, wherein the zirconia ceramic sample to be tested is prepared by the method for preparing a zirconia ceramic sample to be tested for detecting microstructure described in the first aspect.

[0043] The zirconia ceramic sample to be tested provided by the second aspect of the present invention has a short heating and corrosion time, the obtained sample surface is smooth and undamaged, and the subsequent microscope observation and analysis has high accuracy.

[0044] In a third aspect, the present invention provides an application of the zirconia ceramic sample to be tested as described in the second aspect in microscopic observation and detection.

[0045] The zirconia ceramic sample to be tested provided by the third aspect of the present invention has high detection accuracy in microscopic observation and detection, and has broad application prospects.

[0046] Compared with the prior art, the present invention has at least the following beneficial effects:

[0047] (1) The method for preparing the zirconia ceramic sample to be tested provided by the present invention adopts grinding, polishing and heating corrosion in sequence, without the need for chemical corrosion, and the heating corrosion time is short, so as to obtain a zirconia ceramic microstructure with a smooth surface, clear and uniform grain boundary contours, and no damage;

[0048] (2) The heating and corrosion time of the zirconia ceramic sample to be tested provided by the present invention is short, only 0.8 to 1.5 hours, and the surface of the obtained sample is smooth and undamaged. The subsequent microscopic observation and analysis is highly accurate and can be well applied in microscopic observation and detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a surface image of the zirconia ceramic material after polishing in the method for preparing the zirconia ceramic sample to be tested provided in Example 1 of the present invention.

[0050] Figure 2 This is a surface analysis diagram of a zirconia ceramic sample to be tested obtained by the method for preparing a zirconia ceramic sample to be tested provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0053] Example 1

[0054] This embodiment provides a method for preparing a zirconia ceramic sample to be tested, the preparation method comprising the following steps:

[0055] (1) The zirconia ceramic sample was first ground at 300 rpm. During the grinding process, the zirconia ceramic sample was rotated 90° every 5 minutes. The grinding included 4 sub-grindings (the sandpaper mesh numbers used were 240 mesh, 400 mesh, 800 mesh and 1000 mesh, respectively). The sub-grinding time was 20 minutes to obtain the ground sample.

[0056] The ground sample is sequentially subjected to three sub-polishing steps, wherein the first sub-polishing step is performed using a diamond polishing paste of model W14, the second sub-polishing step is performed using a diamond polishing paste of model W7, and the third sub-polishing step is performed using a diamond polishing paste of model W1, to obtain a pre-treated zirconia ceramic sample;

[0057] (2) the pre-treated zirconia ceramic sample is ultrasonically cleaned and dried in sequence to obtain a dried sample;

[0058] (3) The dried sample in step (2) is placed in a pressureless high-temperature sintering furnace, heated to 1350°C at a heating rate of 5°C / min and kept at the final temperature for 1 hour to perform heating corrosion, and then cooled to room temperature at 5°C / min to obtain a zirconia ceramic sample to be tested that can show a microstructure.

[0059] Example 2

[0060] This embodiment provides a method for preparing a zirconia ceramic sample to be tested, the preparation method comprising the following steps:

[0061] (1) The zirconia ceramic sample was first ground at 200 rpm. During the grinding process, the zirconia ceramic sample was rotated 88° every 8 minutes. The grinding included 4 sub-grindings (the sandpaper mesh numbers used were 260 mesh, 450 mesh, 800 mesh and 1100 mesh, respectively). The sub-grinding time was 15 minutes to obtain the ground sample.

[0062] The ground sample is sequentially subjected to three sub-polishing steps, wherein the first sub-polishing step is performed using a diamond polishing paste of model W14, the second sub-polishing step is performed using a diamond polishing paste of model W7, and the third sub-polishing step is performed using a diamond polishing paste of model W1, to obtain a pre-treated zirconia ceramic sample;

[0063] (2) the pre-treated zirconia ceramic sample is ultrasonically cleaned and dried in sequence to obtain a dried sample;

[0064] (3) The dried sample in step (2) is placed in a pressureless high-temperature sintering furnace, heated to 1400°C at a heating rate of 5.5°C / min and kept at the final temperature for 1.5 hours for heating corrosion, and then cooled to room temperature at 8°C / min to obtain a zirconia ceramic sample to be tested that can show a microstructure.

[0065] Example 3

[0066] This embodiment provides a method for preparing a zirconia ceramic sample to be tested, the preparation method comprising the following steps:

[0067] (1) The zirconia ceramic sample was first ground at 400 rpm. During the grinding process, the zirconia ceramic sample was rotated 92° every 3 minutes. The grinding included 4 sub-grindings (the sandpaper meshes used were 200 mesh, 350 mesh, 750 mesh and 900 mesh, respectively). The sub-grinding time was 30 minutes to obtain the ground sample.

[0068] The ground sample is sequentially subjected to three sub-polishing steps, wherein the first sub-polishing step is performed using a diamond polishing paste of model W14, the second sub-polishing step is performed using a diamond polishing paste of model W7, and the third sub-polishing step is performed using a diamond polishing paste of model W1, to obtain a pre-treated zirconia ceramic sample;

[0069] (2) the pre-treated zirconia ceramic sample is ultrasonically cleaned and dried in sequence to obtain a dried sample;

[0070] (3) The dried sample in step (2) is placed in a pressureless high-temperature sintering furnace, heated to 1300°C at a heating rate of 4.5°C / min and kept at the final temperature for 0.8h to perform heating corrosion, and then cooled to room temperature at 3°C / min to obtain a zirconia ceramic sample to be tested that can show a microstructure.

[0071] Example 4

[0072] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the grinding speed in step (1) is 150 rpm, and the details are not repeated here.

[0073] Example 5

[0074] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the grinding speed is 450 rpm, and will not be described in detail here.

[0075] Example 6

[0076] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the sample is not rotated, and will not be described in detail here.

[0077] Example 7

[0078] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that only three sub-grindings are performed, and the grinding mesh sizes are 240 mesh, 400 mesh and 800 mesh respectively, and will not be repeated here.

[0079] Example 8

[0080] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that only the first two sub-polishing steps are performed, and will not be described in detail here.

[0081] Example 9

[0082] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the sample is kept at the final temperature for 2 hours, and will not be described in detail here.

[0083] Example 10

[0084] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the final temperature is kept for 0.5 h, and the details will not be repeated here.

[0085] Embodiment 11

[0086] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the heating rate is 3.5° C. / min, and will not be described in detail here.

[0087] Example 12

[0088] This embodiment provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Embodiment 1 except that the heating rate is 6.5° C. / min, and will not be described in detail here.

[0089] Comparative Example 1

[0090] This comparative example provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as Example 1 except that grinding is not performed, and the details will not be repeated here.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as that of Example 1 except that polishing is not performed, and will not be described in detail here.

[0093] Comparative Example 3

[0094] This comparative example provides a method for preparing a zirconia ceramic sample to be tested. The preparation method is the same as Example 1 except that the heating corrosion is replaced by the chemical corrosion in CN118032473A, and will not be described in detail here.

[0095] Test method: Use a microscope to test the surface structure of the zirconia ceramic sample.

[0096] The surface image of the polished zirconia ceramic material in the preparation method of the zirconia ceramic sample to be tested provided in Example 1 is shown in FIG. Figure 1 The surface analysis diagram of the zirconia ceramic sample to be tested prepared by the preparation method of the zirconia ceramic sample to be tested provided in Example 1 is shown in Figure 2 ,from Figures 1-2 It can be seen that the surface of the zirconia ceramic sample prepared by the present invention is flat and smooth and the metallographic structure is clear.

[0097] The test results of the above embodiments and comparative examples are shown in Table 1.

[0098] Table 1

[0099]

[0100]

[0101] From Table 1, we can see the following points:

[0102] (1) It can be seen from Examples 1 to 3 that the method for preparing a zirconia ceramic sample for detecting microstructure provided by the present invention uses grinding, polishing and thermal corrosion of the zirconia ceramic in sequence, and further optimizes and improves the process. Not only is the metallographic structure clear, but the microstructure is not destroyed, and the application prospect is broad.

[0103] (2) It can be seen from Example 1 and Examples 4 to 5 that the grinding speed in Example 4 is too low, the protrusions and dirt on the surface cannot be removed and the surface is not smooth enough, resulting in unclear metallographic structure. In Example 5, the speed is too fast and may damage the material surface, which may cause overheating or scratches of the material. This shows that the present invention controls the rotation speed within a specific range, and can obtain a sample to be tested with a clear metallographic structure and a complete microstructure.

[0104] (3) Combining Example 1 and Example 6, it can be seen that when the sample is not rotated in Example 6, the polishing liquid is unevenly distributed, there are quality differences on the sample surface, and the metallographic structure surface is not clear. This shows that the present invention rotates the sample during the polishing process to improve the clarity of the metallographic structure.

[0105] (4) It can be seen from Example 1 and Examples 7 to 8 that the grinding and polishing steps have a significant impact on the clarity of the final metallographic structure. The present invention preferably obtains a sample with a clearer metallographic structure through a specific step process.

[0106] (5) It can be seen from Example 1 and Examples 9 to 12 that a too long holding time or a too slow heating rate can easily lead to grain growth, data distortion, and unclear metallographic structure. A too short holding time or a too fast heating rate can easily lead to incomplete volatilization of the material at the grain boundary and inability to fully reveal the grains. This shows that the present invention preferably controls the heating rate and holding time within a reasonable range, which can be coordinated with the previous grinding and polishing steps to better improve the clarity of the metallographic structure and the complete retention of the microstructure.

[0107] (6) In Comparative Example 1, grinding was not performed, the protrusions and dirt on the surface could not be removed, and the metallographic structure was unclear; in Comparative Example 2, polishing was not performed, the scratches on the surface could not be completely removed, and the grains were disturbed; in Comparative Example 3, chemical corrosion was used, and the metallographic structure was unclear.

[0108] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a zirconia ceramic sample for detecting microstructure, characterized in that: The preparation method comprises the following steps: (1) The zirconia ceramic sample is ground and polished in sequence to obtain a pre-treated zirconia ceramic sample; (2) The pre-treated zirconia ceramic sample in step (1) is heated and corroded to obtain a zirconia ceramic sample to be tested that can display a microstructure.

2. The preparation method according to claim 1, characterized in that: The zirconia ceramic sample in step (1) is a zirconia ceramic sample that has been cold-mounted in a mold.

3. The preparation method according to claim 1 or 2, characterized in that: The grinding speed is 200-400 rpm; Preferably, during the grinding process, the zirconia ceramic sample is rotated every 3 to 8 minutes; Preferably, the rotation angle is 88-92°.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The grinding includes at least 3 sub-grindings, preferably 4 sub-grindings; Preferably, the grinding time of each sub-grinding is 15 to 30 minutes.

5. The preparation method according to any one of claims 1 to 4, characterized in that: As the grinding progresses, the mesh size of the sandpaper used in the sub-grinding gradually increases; Preferably, the difference in mesh size between the sandpapers used for adjacent sub-grindings is 200 to 400 meshes; Preferably, when the grinding is performed with four sub-grinding steps, the mesh sizes of the sandpaper used for each sub-grinding step are 200-260 meshes, 350-450 meshes, 750-850 meshes and 900-1100 meshes respectively.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The polishing includes at least 3 sub-polishings, preferably 3 sub-polishings; Preferably, when the polishing is performed with three sub-polishing steps, the first sub-polishing step is performed with a diamond polishing paste of model W14, the second sub-polishing step is performed with a diamond polishing paste of model W7, and the third sub-polishing step is performed with a diamond polishing paste of model W1; Preferably, the preparation method further comprises a cleaning and drying process provided between step (1) and step (2), wherein the cleaning and drying process comprises pre-treating the zirconia ceramic sample by ultrasonic cleaning and drying in sequence.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The heating rate of the heating corrosion is 4.5-5.5°C / min; Preferably, the final temperature of the heating corrosion is 190-210° C. lower than the sintering densification temperature of the zirconia ceramic sample; Preferably, the final temperature of the heating corrosion is 1300-1400°C; Preferably, the heating corrosion is kept at the final temperature for 0.8 to 1.5 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method further comprises, after the heating and etching, cooling to room temperature; Preferably, the cooling rate is 3-8°C / min.

9. A zirconia ceramic sample to be tested, characterized in that: The zirconia ceramic sample to be tested is prepared by the method for preparing a zirconia ceramic sample to be tested for detecting microstructure according to any one of claims 1 to 8.

10. Use of the zirconium oxide ceramic sample according to claim 9 in microscopic observation and detection.

Citation Information

Patent Citations

  • Sample preparation method for observing internal microstructure of ceramic by scanning electron microscope

    CN111795984A

  • Germanium oxide-doped zirconia ceramic material and preparation method thereof

    CN113387698A

  • Light gray zirconia sintered body as well as preparation method and application thereof

    CN115819080A

  • Metallographic sample preparation and structure display method of zirconia ceramic material

    CN118032473A

  • Thermal etching process of a ceramic under oxidizing conditions

    US6171511B1